A pragmatic service typology: capturing the distinctive dynamics of services in time and space - Glückler, Johannes; Hammer, Ingmar (The service industries journal, 2011)
Many service classifications have provided helpful yet partial perspectives on the heterogeneity of services. This paper reconciles and integrates different earlier classifications into a new holistic typology of the service economy which is based on detailed statistical service sectors. Moreover, the paper assesses the empirical value of this taxonomy to capture the diversity of services development in time and space. A regional analysis of employment data in Germany provides evidence that knowledge intensive as well as business services follow very different sectoral and spatial dynamics than operational and consumer services. This typology yields differential insights in longitudinal and comparative regional analysis of the service economy.
Gesehen am 24.06.2022